Tension strength and design method for thread-fixed one-side bolted T-stub. (1st November 2017) - Liu, Mei; Zhu, Xulin; Wang, Peijun; Tuoya, Wulan; Hu, Shuqing
Highlights: Behaviors of one-side bolted T-stub were studied experimentally. Thread failure mode was observed in test. Design methods for two new failure modes were proposed. Proposed design method could precisely predict the failure modes. Abstract: Failure modes and their corresponding tension strengths of thread-fixed one-side bolted T-stub were investigated experimentally and theoretically. The thread resistances of bolts fixed directly to plates were evaluated by experimental analysis. Except for the three failure modes described in the current Eurocode 3, two new failure modes and their corresponding design methods were proposed, which were (a) hole thread failure and (b) T-stub flange yielding with hole thread failure. Influences of the bolt pre-tension force, the thickness of T-stub flange, the existence of the standard nut, the screw depth of the bolt on the failure mode and the ultimate tension strength were studied. The bolt pre-tension force had little influence on the ultimate tension strength; however, it could improve the initial stiffness of the connection. The ultimate tension strength and tension stiffness of the T-stub increased with the increase in flange thickness. For the T-stub with thin flange, the thread hole could also provide sufficient clamping force to ensure the bolted T-stub not fail by thread failure. The existence of the nut did not improve the yield strength of the T-stub; however, it could prevent the separation of two T-stubs after flange yielding, thus the ultimate tension strength was increased. It depended on the screw depth whether the partially screwed bolt was failed by thread failure or bolt failure. Ultimate tension strengths of the T-stub measured from tests were much higher than those calculated by design equations. And under the design load, the bolted T-stub was still in elastic state, which demonstrated the applicable of the thread-fixed one-side bolted T-stub.